Urban agriculture in the context of contemporary challenges of agricultural law - Goździewicz-Biechońska, Justyna (Przegląd Prawa Rolnego, 2022)
The aim of the considerations is to characterise the phenomenon of urban agriculture from the perspective of contemporary challenges of agricultural law and to justify the need for agricultural research into this legal issue. The starting point of the considerations are theoretical concepts of Roman Budzinowski on the subject and limits of agricultural law as a branch of law. Urban agriculture is a complex phenomenon taking various forms. Its main distinguishing feature is its integration with the ecological-social-economic system of the city. The regulation of urban agriculture is fragmented and varied. However, it does constitute a set of norms that can be regarded as belonging to agricultural law. Consequently, it may constitute an interesting area of research for agricultural lawyers, especially as an exemplification of contemporary challenges and development tendencies of agricultural law.